Injuries in Female Futsal Players: A Systematic Review - Luis Miguel Fernández-Galván; Carlos Hernández Santana; Carlos López-Nuevo; Jorge Sánchez-Infante (MDPI AG, 2024)
Background: Injuries represent one of the most challenging scenarios for both athletes and teams. The aim of this systematic review was to examine the incidence and epidemiological data of injuries in female futsal players. Methods: A systematic search was conducted using PubMed, Scopus, SportDiscus, and Web of Science databases, and subsequently, nine studies were selected. Results: The most frequently damaged area is the ankle (28.15%), followed by the thigh (19.99%), knee (18.41%), and groin (17.26%), according to an analysis of nine studies, seven of which included data on professional futsal players and four of which included amateurs. Elite (28.62%) and amateur futsal players (27.06%) experience ankle injuries almost equally, whereas amateurs suffer thigh injuries (29.41%) far more often than elite athletes (13.71%). The most common injuries are strains (27.05%) and sprains (40.6%), with amateurs suffering from sprains more frequently (51%) than elite athletes (36.44%) and elite athletes suffering from strains more frequently (29.4%) than amateurs (20%). Conclusions: Ankle injuries are the most prevalent in female futsal players, with amateurs particularly prone to sprains. Based on these results, professionals in this field may identify injury patterns that could guide future prevention efforts specifically tailored to female futsal players.